2012
DOI: 10.1016/j.envint.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to pesticide ingredient piperonyl butoxide and childhood cough in an urban cohort

Abstract: Rationale Previously we reported that airborne concentrations of cis-permethrin, but not trans-permethrin, measured during pregnancy in an inner city pediatric cohort was associated with cough by age 5. However, the effect of subsequent exposures to both permethrins during early childhood, and to piperonyl butoxide (PBO, a synergist for residential pyrethroid insecticides) remains to be elucidated. We hypothesized that prenatal and age 5-6 year measures of PBO and permethrins would be associated with cough at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
3
23
1
Order By: Relevance
“…This study found an association between prenatal exposure to PBO and non-infectious cough in children aged 5-6 years (OR 1.27, 95% CI 1.09-1.48, n=217), but not exposure to PBO measured at 5-6 years of age. There was no significant association with cis-and trans-permethrin in the air and cough measured prenatally or at the age of 5-6 years [36].…”
Section: Studies In Childrenmentioning
confidence: 79%
See 3 more Smart Citations
“…This study found an association between prenatal exposure to PBO and non-infectious cough in children aged 5-6 years (OR 1.27, 95% CI 1.09-1.48, n=217), but not exposure to PBO measured at 5-6 years of age. There was no significant association with cis-and trans-permethrin in the air and cough measured prenatally or at the age of 5-6 years [36].…”
Section: Studies In Childrenmentioning
confidence: 79%
“…Moreover, the results of some studies have indicated that early exposure to pesticides up to the age of 4 years is the most relevant time window of exposure [30,31]. It was also shown that contact of the children in the first year of life with a mother who was herself in contact with pesticides in the case of occupational and/or residential exposure was likely to increase the likelihood of wheezing and childhood asthma [39,42], non-infectious cough in children aged 5-6 years [36], and wheezing in children under 18 years of age [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reviews of PBO safety determined cases of subacute and chronic toxicity, including the induction of abnormal pigmentation in chicken feathers (Blankenship et al 2003) and hepatocellular tumors in mice when fed PBO in the diet (Kawai et al 2009). The most pertinent effects to human health were observed in children exposed to PBO in the womb that led to heightened risk of noninfectious cough at ages 5 and 6 years (Liu et al 2012). Because of these and other negative effects, PBO registration may not be renewed and alternative pesticide synergists will be required.…”
Section: Discussionmentioning
confidence: 99%